2020
DOI: 10.3390/antibiotics9060311
|View full text |Cite
|
Sign up to set email alerts
|

Public Hospital Pharmacists’ Perceptions and Knowledge of Antibiotic Use and Resistance: A Multicenter Survey

Abstract: Antimicrobial Stewardship Program (ASP) has been implemented in major public hospitals in Malaysia, with pharmacists playing a key role in ensuring the appropriate use of antibiotics. This survey aimed to assess the practices, perceptions, and knowledge of public hospital pharmacists on antibiotic use and resistance. A cross-sectional survey involving pharmacists from six public hospitals in Penang was conducted using a self-administered validated questionnaire. The majority of pharmacists perceived that polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…This could lead to the rise of antibiotic misprescribing and/or overprescribing, further impacting the development of resistance. Thus, it is important to address one’s knowledge and beliefs of the proper antibiotic usage, hence stopping the misconceptions and expectations of using antibiotics to treat minor illnesses [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could lead to the rise of antibiotic misprescribing and/or overprescribing, further impacting the development of resistance. Thus, it is important to address one’s knowledge and beliefs of the proper antibiotic usage, hence stopping the misconceptions and expectations of using antibiotics to treat minor illnesses [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the rate of interventions on e-prescriptions from paediatric wards in this study was low (3.2%) compared to other wards whereas a study by Cesarz et al (2013) showed the rate of interventions on paediatric prescriptions (23.6%) was higher than adult prescriptions (8.5%). Nonetheless, it is important to note that the specialty wards with ward pharmacists had a significantly higher number of interventions, likely owing to these pharmacists' active participation in clinical rounds, better clinical knowledge, and competence in medication use and recommendations, and thus fostering identification of patient medication needs and related problems [20][21][22]. Similarly, the acceptance rate among prescribers in wards with ward pharmacists on duty was significantly higher than in wards without ward pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…The sale of antibiotics without medical prescription has been observed in many countries [41][42][43]. Globally 62% of antibiotics dispensed in community pharmacy do not have a prescription [9,44,45].…”
Section: Antibiotics Dispensing Behaviourmentioning
confidence: 99%
“…Community pharmacists knowledge about antibiotics and resistance have a significant impact on their dispensing practice [57][58][59]. Those with three to four years of experience knew more about how to use medications correctly than those with nine to ten years of experience [4,41,42]. ABR could be a major factor affecting the illegal and inappropriate supply of antibiotics to patients with mild diseases at community pharmacies because to a lack of information about antibiotics [30].…”
Section: Antibiotics Knowledge and Factors Contributing For Dispensing Without Prescriptionmentioning
confidence: 99%